Basic approaches to the study of intercultural adaptation in foreign psychology - O V Maslova (Peoples' Friendship University of Russia (RUDN University), 2008)
In the article are represented contemporary theoretical and empirical approaches to the study of intercultural adaptation in the foreign psychological literature. The solution of its crucial problems from the positions of these approaches is examined.